2011
DOI: 10.1002/jca.20282
|View full text |Cite
|
Sign up to set email alerts
|

Successful preoperative treatment of a Graves' disease patient with agranulocytosis and hemophagocytosis using double filtration plasmapheresis

Abstract: Agranulocytosis is an uncommon but serious complication of Graves' disease under thionamide therapy. In some patients removal of circulating thyroid hormones and thyroid antibodies by plasmapheresis is an effective adjunctive therapeutic option. In perioperative settings, however, plasmapheresis may cause excess bleeding intraoperatively due to coagulation factor depletion unless fresh frozen plasma (FFP) products are used in the replacement fluid mix. Double filtration plasmapheresis (DFPP) in which only a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Review of the literature of reported cases of agranulocytosis between 1999 and 2013 identified 80 cases where the presenting symptoms were described [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. Fever (93.8%), sore throat (68.7%) and chills (21.2%) were the commonest presenting symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Review of the literature of reported cases of agranulocytosis between 1999 and 2013 identified 80 cases where the presenting symptoms were described [13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37]. Fever (93.8%), sore throat (68.7%) and chills (21.2%) were the commonest presenting symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Two to five courses of TPE were administered in patients with GD or toxic nodular goiter where thyroidal hyperfunction was not controlled by antithyroid drugs. In some instances, TPE was employed when antithyroid drugs were contraindicated, due to such adverse effects as agranulocytosis or hepatotoxicity ( 5 9 10 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…In patients refractive to iodine solution, especially those requiring urgent surgery or those at risk of organ failure from thyrotoxicosis, an alternate modality is needed for appropriate control of thyroid function. Removal of circulating thyroid hormone by therapeutic plasma exchange (TPE) has been reported as a useful adjunct in these instances ( 3 4 5 ). We described a patient with GD who underwent successful sequential TPE and RAI therapy.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in preoperative and post-operative management of severely hyperthyroid patients with contraindications to antithyroid drugs (13). It has also been used for the management of TS, predominantly in patients with Graves' disease with ophthalmopathy (14,15) or agranulocytosis (16,17) and in selected patients with toxic multinodular goiter (18). In a recent case of TS, plasmapheresis was done post surgery, where sleeve pneumonectomy was the precipitating event and the patient had not responded to standard antithyroid treatment (19).…”
Section: Discussionmentioning
confidence: 99%